2010
DOI: 10.1002/syn.20849
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine‐ and morphine‐induced synaptic plasticity in the nucleus accumbens

Abstract: The critical brain areas and molecular mechanisms involved in drug abuse and dependence have been extensively studied. Drug-induced persistent behaviors such as sensitization, tolerance or relapse, however, far outlast any previously reported mechanisms. A challenge in the field of addiction, therefore, has been to identify drug-induced changes in brain circuitry that may subserve long-lasting changes in behavior. The present study examined behavioral changes and electron microscopic evidence of altered synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 96 publications
3
32
0
Order By: Relevance
“…Additionally, these studies were performed in males only. Alcantara et al (2011) recently reported a stereological EM analysis of NAc core and shell synapses in female rats in response to chronic cocaine or morphine; their core spine synapse density data in controls match well with our averaged data for females. However, this study was focused on a more limited rostro-caudal level of the NAc (Bregma 1.2, which falls into our caudal category).…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, these studies were performed in males only. Alcantara et al (2011) recently reported a stereological EM analysis of NAc core and shell synapses in female rats in response to chronic cocaine or morphine; their core spine synapse density data in controls match well with our averaged data for females. However, this study was focused on a more limited rostro-caudal level of the NAc (Bregma 1.2, which falls into our caudal category).…”
Section: Discussionsupporting
confidence: 78%
“…Importantly, this effect is dependent upon the state of cocaine exposure ( in vivo drug experience), since excitatory signaling in the NAc is potentiated following extended withdrawal but depressed following drug re-exposure 111 . Similar differences in synaptic transmission have been obtained following morphine treatment 112 , and gross changes in synapse morphology that mirror the electrophysiology have also been observed 113 . Prior to, and perhaps facilitating these biphasic synaptic changes that occur following extended withdrawal and re-exposure is the generation of silent synapses that occurs acutely following repeated cocaine exposure 114 .…”
Section: What Are the Molecular Mediators Of Addiction Pathology?supporting
confidence: 65%
“…Drug-induced neuronal modifications suggestive of alterations in patterns of synaptic connectivity have been identified in the VTA, nucleus accumbens and mPFC. [124][125][126][127] The changes in dendritic structure in VTA neurons are particularly intriguing because the VTA is a critical site for the initiation of sensitization; administration of amphetamine directly into the VTA is sufficient to produce sensitized DA release in the nucleus accumbens and behavioural response to a subsequent systemic injection of this drug. 122 Blockade of glutamate receptors directly in the VTA during stimulant drug pretreatment prevents the development of sensitization.…”
Section: Sensitization To the Effects Of Stimulant Drugsmentioning
confidence: 99%